The Influence of Price and Network Quality on the Decision of Tri Card Users (A Case Study of Tri Card Consumers in Pondok Baru Village) - Karimi Karimi; Hayanuddin Safri; Rizkha Maulana; Denny Firmansyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to determine the effect of price and network quality on user decisions. Respondents in this study were 70 people from the village of Central Pondok Baru who used the Tri cellular card. Based on the results of multiple linear regression analysis, it was concluded that price and network quality had an effect on usage decisions. In this study using research instruments in the form of validity and reliability tests. Validity means that the instrument can be used to measure what it is supposed to measure. While the instrument reliability means that when used to measure many times will produce the same data. Based on the results of the t test and significance, it is known to have a T Count of 3.327 and a significant level of 0.01 is less than 0.05. It can be concluded that the price variable partially has a significant effect on the user decision variable. This means, the results of the t-test also show the partial influence of network quality on user decisions based on the results of the t-test of 3,048 and a significant level of 0.03 which is smaller than 0.05, so it can be concluded that the product quality variable partially has a significant effect on usage decisions. The results of the F test or t test (simultaneous) show that the variables are price and user quality. This can be seen from the Fhitung of 16.106 > Ftable of 3.13 (16.106> 3.13).